2019
DOI: 10.21685/1680-0826-2019-13-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant single chain antibodies as an instrument to search proteins involved in the interaction of microsporidia and other intracellular parasites with an infected host cell

Abstract: Obligate parasitism of microsporidia-close to fungi protists causing widespread diseases of animals and immunodeficient patients, significantly complicates studies of their relationships with an infected host cell. Since microsporidia cannot be cultivated outside the host cell, genetic manipulations with them are extremely difficult. At the same time, long adaptation of microsporidia to the intracellular lifestyle, drastic minimization of their metabolic machinery, acquisition of unique transporters to exploit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Three years ago, we constructed an immune scFv library against fat body proteins of locust Locusta migratoria infected with the microsporidium Paranosema ( Antonospora ) locustae and selected scFv fragments specific to three secretory proteins of the parasite [ 32 ]. The following sequencing showed that two of them had the same VL domain of a human IgG (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three years ago, we constructed an immune scFv library against fat body proteins of locust Locusta migratoria infected with the microsporidium Paranosema ( Antonospora ) locustae and selected scFv fragments specific to three secretory proteins of the parasite [ 32 ]. The following sequencing showed that two of them had the same VL domain of a human IgG (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…The gel-purified PCR products were cloned into the pSEX81 phagemid vector (Progen Biotechnik, Heidelberg, Germany) at the Nco I/ Hind III (VH domains) and Mlu I/ Not I (VL domains) restriction sites to construct an immune scFv library with a representativeness of about 10 million E. coli transformants (XL1-Blue MRF’ strain). All stages of library constructing, storage, infection with the M13 KO7ΔpIII hyperphage (Progen Biotechnik, Heidelberg, Germany), and phage production have been described previously [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation